Ventilation System Simulation Model at a Mine - Artica, I. (2019)
This research project modeled and simulated a ventilation system at a Mining Concession, obtaining real-time information regarding the fans used to ventilate the mine. The simulation was developed using the VENTSIM 5 software, which also helped define the number of fans and the operating parameters required, field information, mine dimensions, the mining method, production, geothermal gradient, gas emission, air stream, and air pressure. In addition, the results from software operation revealed the need to open chimneys and use fans. Furthermore, the results also suggest that a specialist dedicated to ventilation and fan maintenance must be hired to formalize mining operations as per the Occupational Safety and Health Mining Regulations from Executive Action No. 024-2016-EM as this Mining Concession is currently operating without license.